Is open-label placebo a new ergogenic aid? A commentary on existing studies and guidelines for future research - Saito, T.; Barreto, G.; Saunders, B.; Gualano, B. (Sports Medicine, 2020)
Key Points An open-label placebo intervention, when individuals are openly told that they are receiving an inert treatment, has been shown to improve disease symptoms of clinical populations. Open-label placebo has recently been implemented in sport and exercise studies, with contrasting results on exercise performance. It is imperative that further well-designed studies are conducted to elucidate the true ergogenic potential of open-label placebo and the associated mechanisms.